A preliminary study on microplastics contamination in wild fishes caught from urbanised Sepanggar river of Kota Kinabalu, Sabah - Raveena Kaur Kalwant-singh; Soo, Chen Lin; Chen, Cheng Ann (Universiti Malaysia Sabah, 2025)
Urban areas with high population densities generate high levels of plastic waste from human activities, potentially raising microplastic levels in riverine systems. Microplastic pollution in rivers pose serious risks to fish through ingestion, toxicity, and bioaccumulation. Nevertheless, the paucity of previous studies on fish microplastic contamination in Sabah, Malaysia highlights knowledge gaps in this area. Thus, this study aimed to provide a preliminary assessment of microplastic contamination in fish from the urbanised Sepanggar River in Kota Kinabalu, Sabah. A total of 39 fish samples were caught from the river, dissected into muscles and internal organs, and digested with 10% potassium hydroxide (KOH). Microplastics were then extracted using the density separation method in 5M sodium chloride (NaCl) and counted by shape, colour, size, and polymer type. The present study demonstrated that microplastics were detected in 77% of fish caught from the Sepanggar River, with an average of 5.28 ± 6.51 items/fish. Small-sized (97%), fragment (54%) and black colour (40%) were the most prevalent characteristics of microplastics found in fish while rayon (23%) was the most prevalent polymer type. Microplastic abundance in internal organs (3.54 ± 3.63 items/fish) was significantly higher than that in muscles (1.74 ± 5.10 items/fish). The characteristics of ingested microplastics varied significantly by fish species, most likely due to the different feeding habits and diets. This study provides the first confirmation that fish in the Sepanggar River were contaminated by microplastics from adjacent domestic and industrial activities. Improved waste management is needed to monitor and reduce long-term microplastic pollution.